2012
DOI: 10.1007/978-1-62703-071-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Diagnostic Potential of Immune Biomarker Coexpression in Gulf War Illness

Abstract: Complex disorders like Gulf War Illness (GWI) often defy diagnosis on the basis of a single biomarker and may only be distinguishable by considering the coexpression of multiple markers measured in response to a challenge. We demonstrate the practical application of such an approach using an example where blood was collected from 26 GWI, 13 healthy control subjects, and 9 unhealthy controls with Chronic Fatigue at three points during a graded exercise challenge. A 3-way multivariate projection model based on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
4
18
0
Order By: Relevance
“…[1][2][3] Our work and that of others strongly suggest that pathogenesis of this complex illness includes an immunologic [4][5][6][7] and an endocrine component. 8 Based on this, we proposed an illness model whereby GWI may involve a chronic imbalance in co-regulation between the nervous, endocrine and immune systems.…”
Section: Introductionmentioning
confidence: 42%
See 1 more Smart Citation
“…[1][2][3] Our work and that of others strongly suggest that pathogenesis of this complex illness includes an immunologic [4][5][6][7] and an endocrine component. 8 Based on this, we proposed an illness model whereby GWI may involve a chronic imbalance in co-regulation between the nervous, endocrine and immune systems.…”
Section: Introductionmentioning
confidence: 42%
“…Comparison with a broad set of immune and endocrine markers measured in peripheral blood from GWI subjects 4,5 indicated that this chronic condition is proximal to such alternate homeostatic regimes and that homeostatic drive may be involved in the perpetuation of illness. 10,11 Specifically, we found that that the inclusion of basic immune function and male sex hormone regulation by the HPG axis with HPA function resulted in the emergence of 5 stable equilibrium states.…”
Section: Introductionmentioning
confidence: 45%
“…Response to exercise and other stressors has the potential to be very different in these new regulatory regimes. This is something that we have observed firsthand in our work with human GWI and CFS subjects [68]. As these models are based on currently documented knowledge of human physiology and regulatory biochemistry they are necessarily incomplete.…”
Section: Discussionsupporting
confidence: 42%
“…In contrast, male GWI could not be distinguished easily from their CFS counterparts on the basis of minimally overlapping cytokine markers as these typically trended in the same direction compared to control. Separation of these subjects was achieved in previous work by our group [28] but this work made extensive use of cytokine response measured in supernatants isolated and treated in vitro with the mitogen phytohaemagglutinin (PHA), a stimulant of T cell activity. The current work would suggest these groups may share several features of cytokine co-expression in plasma and that the patterns and levels obtained in response to in vitro stimulation with a specific mitogen may be required to provide the resolution necessary to distinguish one set from the other unequivocally.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis we hypothesize that lack of agreement in the above mentioned studies of cytokine signatures in these illnesses may be linked at least in part to sex-specific differences in endocrine-immune cross-talk that are also illness-specific. Preliminary work by our group using an exercise paradigm in a pilot-scale cohort of male GWI subjects (n = 10 training set, 16 validation set, age 42 ± 1.2 [33–58 years]) indicated noticeable gender and illness-specific differences in an abbreviated panel of plasma and PHA-stimulated cytokines with levels found in male CFS subjects (n = 9, age 42 ± 2.8 [28–56 years]), and female GWI subjects (n = 10, 47 ± 2.0 [38–58 years]) [28]. Indeed a large number of existing studies have been carried out in cohorts that consist of either male or female subjects.…”
Section: Introductionmentioning
confidence: 99%